Lutas por direitos trabalhistas de canavieiros do Brejo Paraibano durante o contexto da redemocratização (Usina Santa Maria, 1987-1988) - Silva, Raquel Rocha da (2024)
This work aims to analyze the struggle for labor rights of former workers at the Santa Maria sugar and alcohol plant, located in the municipalities of Areia, Pilões and Serraria, in the state of Paraíba. The time frame covers the years 1987 and 1988, which mark the first years of the implementation of the Conciliation and Judgment Board in the city of Guarabira. Usina Santa Maria employed around four thousand and forty workers and was the largest agricultural enterprise in the Brejo Paraibano region. In the 1980s, however, the crisis of PROÁLCOOL and the sugar and alcohol sector culminated in the closure of this plant, generating mass unemployment in the region. The period of study is situated in the context of consolidation of Brazilian redemocratization, when the presence of the Labor Court begins to represent expectations for workers regarding the emergence of new opportunities and instruments to fight for labor rights. We will use as research sources the records of the Guarabira Conciliation and Judgment Board, linked to the Regional Labor Court of the 13th Region (TRT-13), corresponding to the state of Paraíba, and which are available at the Historical Documentation Center of the Humanities Center from the State University of Paraíba (NDH-CH/UEPB) and, the iconographic documents from the Popular Education Service (SEDUP), located in the city of Guarabira/PB.